Prioritization of criteria in teacher-candidate selection process by a pairwise comparison method - Mat Kasim, Maznah; Ramli, Razamin; Ibrahim, Haslinda; Ghazali, Mohd Izam; Mohmad Kamal, Fazillah; Vikneswari, S. (2012)
Teacher quality is the most important single variable in students’ learning process.As the country is moving towards a knowledge- based society, selecting qualified teachers to enter the training programs is very crucial. This paper reviews and identifies the criteria used in the teacher-candidate selection process.A group of experts which consists of those who have experience in conducting the related interviews was asked to give opinions and to judge the criteria and the sub-criteria according to their importance. A multi-criteria method, Analytic Hierarchy Process (AHP) is used to analyze the judgments.Generally, the results of the analysis show that ‘communication skills’ and ‘personality’ as the most and second most important criteria respectively, followed by ‘content of knowledge’ as in the third position.The analysis of the importance of the sub-criteria of these three main criteria is also included.